Os textos sincréticos no Enem: uma análise semiótica - Pontes Júnior, José Leandro Gonçalves de (2020)
It is, above all, with the development of information and communication technologies that texts have been produced, increasingly, in a syncretic manner, that is, from the combination of manifestation languages. Syncretic text is present in the physical and virtual spaces, in the most diverse social practices. In addition to its presence in public and private demands, the syncretic text is also present in the National High School Exam (Enem), an important national level assessment that, among other purposes, aims to measure student performance at the end of schooling basic. With the proliferation of syncretic text in different spaces, there is a need to understand the way it has been approached. Thus, this work aims to understand, specifically, its approach in the Enem test or, in other words, to understand the type of reading requested from candidates. To this end, this work draws on the theoretical and methodological postulates of discursive semiotics, above all, on the discussions undertaken by Greimas, Barros, Fiorin and Teixeira. The corpus of analysis consists of questions from the Language, Codes and their Technologies test from 2010 to 2019. The analysis of the questions is made possible through a script that considers the examination of the text content plan, its verbovisual expression plan, the articulation between the content plan and the verbovisual expression plan and the examination of the statement of the questions. From the analysis undertaken, it was found that, in most questions, a verbovisual reading is not requested, that is, there is a tendency for the articulation between the manifestation languages in interaction not to be approached.